Nurse Practitioners in Swiss Family Practices as Potentially Autonomous Providers of Home Visits: An Exploratory Study of Two Cases. Issue 1 (February 2021) - Gysin, Stefan; Bischofberger, Iren; Meier, Rahel; van Vught, Anneke; Merlo, Christoph; Essig, Stefan
In Swiss primary care, general practitioner (GP) home visits have decreased due to impending GP shortages particularly in rural areas. Nurse practitioners (NP) are newly introduced in family practices and could potentially offer home visits to the increasing number of multimorbid elderly. We analysed consultation data from two pilot projects (Practice A and Practice B) with the goal to measure the frequency and patient characteristics of NP consultations both in the practice and on home visits, and to determine the NPs' autonomy based on the required GP supervision. In Practice A, 17% of all NP consultations were home visits, in Practice B 51%. In both practices, the NPs saw older patients and reported higher autonomy on home visits compared to consultations in the practice. In Practice A, the NP encountered a higher share of multimorbid patients on home visits than in the practice, and the NP's proportion of autonomously conducted consultations increased from 0% in the first month to 19% after 13 months of GP supervision. In Practice B, the NP was autonomous in about three-quarters of consultations after 2 years on the job. These first cases provide some evidence that NPs could reach a relatively high degree of autonomy and might pose a potential solution for the decreasing numbers of GP home visits to multimorbid elderly in Swiss primary care.